2000
DOI: 10.1289/ehp.00108s3451
|View full text |Cite
|
Sign up to set email alerts
|

Identifying critical windows of exposure for children's health.

Abstract: Several authors have considered the importance of exposure timing and how this affects the outcomes observed, but no one has systematically compiled preconceptional, prenatal, and postnatal developmental exposures and subsequent outcomes. Efforts were undertaken to examine the information available and to evaluate implications for risk assessment for several areas: a) respiratory and immune systems, b) reproductive system, c) nervous system, d) cardiovascular system, endocrine system, and general growth, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
257
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(265 citation statements)
references
References 30 publications
0
257
0
3
Order By: Relevance
“…The enduring influence of an insult depends on the maturational stage of the brain and to what extent the normal developmental trajectory is disrupted (Andersen, 2003). Epidemiological data supports the concept that the time of exposure may be essential to some types of stressors, as similar adverse events occurring at early or late stages have been associated with differing outcomes (Selevan et al, 2000, Meyer et al, 2011. Stress and infection occurring during gestation or in early life can differentially increase the risk of several distinct disorders (Glynn et al, 2001, Bale et al, 2010, Brown, 2012, Howerton and Bale, 2012.…”
Section: Adverse Events and Brain Development-importance Of Timingmentioning
confidence: 87%
“…The enduring influence of an insult depends on the maturational stage of the brain and to what extent the normal developmental trajectory is disrupted (Andersen, 2003). Epidemiological data supports the concept that the time of exposure may be essential to some types of stressors, as similar adverse events occurring at early or late stages have been associated with differing outcomes (Selevan et al, 2000, Meyer et al, 2011. Stress and infection occurring during gestation or in early life can differentially increase the risk of several distinct disorders (Glynn et al, 2001, Bale et al, 2010, Brown, 2012, Howerton and Bale, 2012.…”
Section: Adverse Events and Brain Development-importance Of Timingmentioning
confidence: 87%
“…Early pregnancy is a critical window of fetal development and exposure to environmental contaminants during this time period may adversely impact the pregnancy as well as neonatal, early childhood, and later life outcomes (Gluckman et al, 2008;Selevan et al, 2000). Previous studies have suggested that prenatal exposure to metals, such as lead, mercury, cadmium, and arsenic, may adversely affect fetal growth (Drouillet-Pinard et al, 2010;Gundacker et al, 2010;Kippler et al, 2012;Lin et al, 2011;Menai et al, 2012;Schell et al, 2009;Xie et al, 2013;Zhu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, elevated gastric absorption of inorganic elements is observed in infants and preschool-aged children compared to adults (Makri et al 2004). Dermal absorption and inhalation uptake of environmental chemicals may be enhanced in infants due to thinner skin as well as greater skin and lung surface area, and increased ventilation rates (Silvaggio and Mattison 1993;Selevan et al 2000;Scheuplein et al 2002;Makri et al 2004).…”
Section: Introductionmentioning
confidence: 99%